Endophytic cultivable bacterial community obtained from the Paullinia cupana seed in Amazonas and Bahia regions and its antagonistic effects against Colletotrichum gloeosporioides. (September 2016) - Silva, Maria Carolina Santos e; Polonio, Julio Cesar; Quecine, Maria Carolina; Almeida, Tiago Tognolli de; Bogas, Andréa Cristina; Pamphile, João Alencar; Pereira, José Odair; Astolfi-Filho, Spartaco; Azevedo, João Lucio
Abstract: Guarana ( Paullinia cupana var. sorbilis ) is a plant from the Amazonas region with socio-economic importance. However, guarana production has been increasingly affected by unfavorable conditions resulting from anthracnose, caused by the Colletotrichum fungal genus, which primarily affects mainly the Amazonas region. The aim of the present study was to isolate bacterial endophytes from the seeds of guarana plants obtained from Amazonas region and the Northeast state of Bahia, a region where this disease is not a problem for guarana plantations. The number of bacterial Colony Forming Units (CFU/g seeds) was 2.4 × 10 4 from the Bahia and 2.9 × 10 4 from the Amazonas region. One hundred and two isolated bacteria were evaluated in vitro against the phytopathogenic strain Colletotrichum gloeosporioides L1. These isolates were also analyzed for the enzymatic production of amylase, cellulase, protease, pectinase, lipase and esterase. Approximately 15% of isolates, showing high antagonistic activity, and the production of at least one enzyme were identified through the partial sequencing of 16S rDNA. The genus Bacillus was the most frequently observed, followed by Paenibacillus, Ochrobactrum, Microbacterium and Stenotrophomonas . Proteolytic activity was observed in 24 isolates followed by amylolytic, pectinolytic and cellulolytic activities. No esterase and lipase production was detected. Most of the isolates, showing antagonistic effects against C. gloeosporioides and high enzymatic activities, were isolated from the anthracnose-affected region. A biocontrol method using the endophytes from guarana seeds could be applied in the future, as these bacteria are vertically transferred to guarana seedlings. Graphical abstract: Highlights: Endophytic bacteria were isolated from seeds of guarana. The endophytic diversity from different Brazil regions was evaluated. Isolates from the anthracnose-affected region show antagonistic activities. Endophytic bacterial isolated from guarana seeds can produce enzymes.